Association of Mean Pressure Gradient, Pressure Half Time, Regurgitant Area, and Heart Rate with Mitral Valve Orifice Area Prior and Post Edge-To-Edge Mitral Valve Repair - Dykun, Iryna; Lüdike, Peter; Poyraz, Sultan; Lind, Alexander Y.; Rassaf, Tienush; Mahabadi, Amir A. (Cardiology and Cardiovascular Medicine, 2021)
Background: Mitral valve orifice area (MVOA) is a key parameter in edge-to-edge mitral valve repair. 3-dimensional transesophageal echocardiography (TOE) assessment of MVOA is the gold standard. In clinical routine, mitral valve stenosis is frequently estimated by mean pressure gradient (MPG) and pressure half time (PHT), which are influenced by the degree of regurgitation and heart rate (HR). Objectives: We aimed to determine the association of MPG, PHT, regurgitant area, and HR with MVOA with mitral valve regurgitation in patients undergoing interventional mitral valve repair. Methods: TOE images from patients undergoing edge-to-edge mitral valve repair were evaluated. MVOA was measured from 3-dimensional volume datasets using multiplanar reformations. Linear regression analysis was used to determine the association of MPG and PHT with MVOA. Results: By implantation of 1.24 devices in 51 patients (aged 80±13years, 49%male), MVOA was reduced from 5.77±2.17cm² to 2.96±1.03cm². MVOA was modestly inversely correlated with MPG (r=-0.45, p<0.0001) and PHT (r=-0.56, p<0.0001). MPG (unadjusted Beta-estimate (95%CI):-0.99(-1.38–0.60), p<0.0001, r-square=0.20) and PHT (-1.23(-1.59–0.87), p<0.0001, r-square=0.31) were significantly associated with MVOA. Prediction of MVOA improved when combining the information of MPG, PHT, HR and regurgitant area (r-square=0.516). Conclusion: MPG and PHT modestly predict 3-dimensional MVOA. However, only combining the information of MPG and PHT with patient’s HR and regurgitation allows reliable prediction of MVOA.